2011
DOI: 10.1002/jat.1663
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity testing using pluripotent stem cell‐derived human cardiomyocytes and state‐of‐the‐art bioanalytics: a review

Abstract: In this article, recent progress in cardiotoxicity testing based on the use of immortalized cell lines or human embryonic stem cell (hESC) derived cardiomyocytes in combination with state-of-the-art bioanalytical methods and sensors is reviewed. The focus is on hESC-derived cells and their refinement into competent testing cells, but the access and utility of other relevant cell types are also discussed. Recent developments in sensor techniques and bioanalytical approaches for measuring critical cardiotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 94 publications
0
43
0
Order By: Relevance
“…Cardiovascular toxicity is a major cause of drug withdrawal during clinical development, accounting for up to 33% of drug failure (MacDonald and Robertson, 2009). Approximately half of these are due to risk of arrhythmias, including QT prolongation and life-threatening polymorphic ventricular tachycardia or torsade de pointes (TdP) (Mandenius et al, 2011). Part of the reason for this failure in early pharmacological screening is that our current testing systems do not accurately replicate human cardiovascular conditions, particularly cardiac electrophysiology, and cannot account for individual variability.…”
Section: Drug Discovery and Toxicology: The Need For A New Experimentmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular toxicity is a major cause of drug withdrawal during clinical development, accounting for up to 33% of drug failure (MacDonald and Robertson, 2009). Approximately half of these are due to risk of arrhythmias, including QT prolongation and life-threatening polymorphic ventricular tachycardia or torsade de pointes (TdP) (Mandenius et al, 2011). Part of the reason for this failure in early pharmacological screening is that our current testing systems do not accurately replicate human cardiovascular conditions, particularly cardiac electrophysiology, and cannot account for individual variability.…”
Section: Drug Discovery and Toxicology: The Need For A New Experimentmentioning
confidence: 99%
“…cardiac troponin T, a clinically valuable marker for cardiomyocyte damage. Multi-wavelength spectroscopy fluorescence can provide real-time information on the protein level of the culture and detect a decrease in this level in the presence of toxic substances due to decrease in cell growth, excretion of proteins from dying cells, and detachment of dying cells from the plate (Mandenius et al, 2011).…”
Section: High-throughput Systemsmentioning
confidence: 99%
“…[7][8][9] These cells have received much attention because of their potential as tools for drug efficacy/safety screenings. 10,11 For example, in drug safety screening, electrophysiological assays including the human Ether-ago-go Related Gene (hERG) inhibition and QT prolongation using hiPS-CMs might predict clinical outcomes, such as arrhythmia. [12][13][14] Although these studies demonstrated the utility of hiPS-CMs at day 20 to 40 of differentiation in electrophysiological analyses, it has been reported that functional sarcoplasmic reticulum (SR) for calcium handling in hESC-derived cardiomyocytes at day 25 to 31 of differentiation is less mature than those in the adult heart 15 and that the functional and morphological maturation depends on the duration of culture.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiomyocytes derived both from hESC and iPS cells have many potential applications in the pharmaceutical industry including target validation, screening and safety pharmacology. These cells would serve as an inexhaustible and reproducible human model system and preliminary reports of the validation of hESC-CM system already exist , Mandenius et al, 2011.…”
Section: Drug Screening and Safety Pharmacologymentioning
confidence: 99%